STUDY OF PHYSICAL-MECHANICAL PROPERTIES OF FABRICS USED FOR MEN'S OUTER KNIT ASSORTMENT - Azimova, Sayyora; Nabidjanova, Nargiza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Objective. The purpose of this scientific research is to study the physical and mechanical properties of rubber textile fabrics produced in our Republic for the development of men's outerwear collections based on the combination of usable residual waste of leather fabrics. Methods. In the "Textile Products Testing" laboratory of the "Knitting Technology" department of the Namangan Institute of Textile Industry, the technological parameters of the upper knitted fabrics made of various raw materials and their physical and mechanical properties were determined experimentally. Results. Physico-mechanical properties of test samples were studied in the research laboratory of the institute on the basis of state standards. The results of the experiment were analyzed and textile fabrics for men's outerwear suitable for the modern fashion trend were selected. Conclusion. Based on the analysis of the high quality indicators of the physical and mechanical characteristics of the upper knitted fabrics produced in the Namangan region, the conclusions of the scientific research on the recommendation for the men's assortment were given.